SIFAT PAPAN WOL KAYU DARI KAYU SENGON DAN KAYU KARET PADA BEBERAPA MACAM UMUR - l M Sulastiningsih; Adi Santoso; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The results of laboratory test of wood-wool board properties made from rubberwood (Hevea brasiliensis) and sengon (Paraserianthes falcataria) are reported in this paper. The wood used were obtained feom different age groups i.e. 10 and 20 years for rubberwood and 5, 10 and 15 years for sengon. The properties tested were board density, moisture content, thickness reduction due to compression and bending strength.The physical and mechanical properties of sengon wood-wool board which the wood-wool was soaked in cold water for 24 hours prior to board fabrication were improved. However, that treatment did not improve the properties of rubberwood wood-wool board. The properties of wood-wool board made from different age groups of tree seem to be similar.